Targeting the Exchange Rate : Empirical Investigation. (IMF Working Papers; Working Paper ;, 1990)
The purpose of this paper is to implement empirically the new theory of exchange rate targeting. The theory formulates an expectations induced relationship between the exchange rate and the fundamental subject to random shocks and target zone constraints. By using monthly data for a representative small-open economy (Israel in the 1980s) the empirical analysis identifies the special roled played by policy and market fundamentals in the behavior of the exchange rate.